2018
DOI: 10.19044/esj.2018.v14n6p336
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kinesio Taping in Reducing Myofascial Pain Syndrome on the Upper Trapezius Muscle: A Systematic Review and Meta-Analysis

Abstract: Background: Myofascial Pain Syndrome is a condition causing pain at myofascial trigger points. Kinesio Taping has been widely used to decrease pain and improve range of motion. Objective: The purpose of this systematic review and meta-analysis was to evaluate the effectiveness of therapeutic programs that include kinesio taping on reducing myofascial pain syndrome symptoms. Methods: Independent research was performed for legit studies using the following electronic databases: PubMed, CINAHL, MEDLINE, SPORT Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
0
11
0
5
Order By: Relevance
“…As a non-invasive treatment, kinesio taping has been gradually used by physiotherapists or pain clinicians in the pain clinic as a clinical support treatment for myofascial pain syndrome or myofascial trigger points. 7,8 However, no consensus has been reached about the benefits of kinesio taping to myofascial pain syndrome or myofascial trigger points. In 2015, Halski et al 9 compared the short-term effects of kinesio taping, cross taping and sham taping for latent upper trapezius myofascial trigger points and reported no significant differences in almost all measurements among the groups.…”
mentioning
confidence: 99%
“…As a non-invasive treatment, kinesio taping has been gradually used by physiotherapists or pain clinicians in the pain clinic as a clinical support treatment for myofascial pain syndrome or myofascial trigger points. 7,8 However, no consensus has been reached about the benefits of kinesio taping to myofascial pain syndrome or myofascial trigger points. In 2015, Halski et al 9 compared the short-term effects of kinesio taping, cross taping and sham taping for latent upper trapezius myofascial trigger points and reported no significant differences in almost all measurements among the groups.…”
mentioning
confidence: 99%
“…Unlike global substantial research on MPS yet inconsistencies concerning its diagnostic criteria, structure of MTrP, etiopathogenesis and pathophysiology, interventions and overall outcome persist in the relevant literature. Furthermore, there is exceedingly scanty literature on myofascial pain syndrome in Saudi Arabia [9]. This research will fill up some gaps in the pragmatic knowledge of professionals including physiotherapists, rehabilitation workers, osteopaths and chiropractors concerned with myofascial pain and MPS practices in Saudi Arabia and other Arabian Gulf countries.…”
Section: Aimmentioning
confidence: 99%
“…These physical and manual therapies under the umbrella of CAM modalities are considered first line treatments in acute MPS [1][2][3]6,9,10,16,20]. Nonsteroidal anti-inflammatory drugs and other analgesics (ibuprofen, diclofenac, aspirin, etc) and muscle relaxants (Methocarbamol, Baclofen, oxazepam, diazepam etc) are often prescribed to patients with MPS, and myofascial pain (MP) linked with regional pain syndromes [1][2][3][4]6,19,42], for reducing muscle spasm and common pain.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Ana Claudia in year 2008 concluded that different techniques of stretching in combination with manual therapy techniques were effective in improving neck pain, ranges and quality of life among females. It was suggested in the study that stretching exercises should be recommended as part of treatment regime in patients with chronic neck pain 20 . Effects of kinesiotaping and postural exercises have also been investigated on parameters on pain, NDI and upper trapezius activity in which it was observed that the effects of kinesiotaping are more effective in reducing pain and other outcome measures than postural exercises 21 .…”
Section: Introductionmentioning
confidence: 99%